MULTI-NUTRIENT FUNCTIONAL BEVERAGES FOR REHABILITATION AND PREVENTION OF POST-TRAUMATIC STRESS DISORDERS - KURYLENKO, YULIA; SUKHENKO, VLADYSLAV; ANDRONOVYCH, GALINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The research outlines the outcomes of developing and investigation of multi-nutrient functional beverages created from natural plant-based raw materials with neuroprotective and adaptogenic properties. The aim of the research was to justify the selection of components that contribute to enhancing the body’s resistance to negative external influences, improving nervous system function, and promoting overall recovery of the psycho-emotional state of individuals during rehabilitation and prevention of post-traumatic stress symptoms. The main ingredients used were natural juices — orange, apple, sea buckthorn, and elderberry — which are sources of vitamins, organic acids, and antioxidants. Additionally, the formulation included lemon balm extract, which has a calming effect, flax seeds — a source of polyunsaturated fatty acids and plant protein, as well as sprouted cereal grains enriched with B-group vitamins and trace elements. Three beverage samples were produced and subjected to physicochemical and organoleptic evaluations. The content of major macroelements (magnesium, calcium, potassium, sodium), which play an important role in maintaining the functions of the nervous and cardiovascular systems, was determined. Organoleptic assessment was conducted using a five-point scale, considering appearance, color, aroma, taste, consistency, and aftertaste. The analysis showed that sample No. 2 demonstrated the highest quality indicators, receiving the highest ratings from tasters for taste, aroma, and consistency. The results confirm the feasibility of using the proposed formulation and component composition for creating functional beverages with enhanced biological value. The developed beverage may be recommended for the diets of individuals experiencing intense physical or mental stress, to support energy balance, prevent nervous exhaustion, and improve overall well-being.